Aligned/unaligned conducting polymer cryogels with three-dimensional macroporous architectures from ice-segregation-induced self-assembly of PEDOT-PSS - Zhang, Xuetong (Langmuir : the ACS journal of surfaces and colloids, 2011)
Porous conducting polymers are of great interest because of the huge potential to combine high surface areas in the dry state with physical properties relevant to organic electronics. Aligned or unaligned conducting polymer cryogels with 3D macroporous architectures have been prepared using the ice-segregation-induced self-assembly (ISISA) of different poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT-PSS) freezing precursors as a dispersion or a formed hydrogel. The chemical composition and molecular structure of the resulting conducting polymer cryogels have been investigated by X-ray photoelectron spectroscopy and Raman spectroscopy, respectively. The morphologies of the PEDOT-PSS cryogels, together with their textural structures, have been revealed by scanning electron microscopy, mercury porosimetry, and nitrogen sorption tests. Processing PEDOT-PSS via ISISA endows the conducting polymers with novel properties, as demonstrated by a series of X-ray diffraction, differential scanning calorimetry, and electrical conductivity tests. These conducting polymer cryogels with aligned/unaligned macroporous architectures suggest the potential in the development of electronic components, tissue engineering, and next-generation catalytic and separation supports